Edukasi PHBS: Membangun Kesadaran pada Siswa SDN Potrobangsan 3 Magelang - Sukmaningtyas, Langen; Fadhillah, Annisa; Nadifa, Masna An; Purnama, Aji Yudha; Kurniawan, Widyadhana Nafi; Nugraha, Joko Tri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The importance of maintaining health, especially for school-age children, is not always related to their freedom from various acute diseases, but also concerns the process of physical growth and development, cognitive development, and the formation of lifelong habits. Clean and Healthy Living Behavior (PHBS) is a strategic effort to improve public health by disseminating healthy lifestyle experiences to individuals, groups, and communities through communication as a means of sharing information. The method used in this community service activity is a participatory approach through outreach and mentoring for students. From several series of activities that have been carried out, it was found that the objectives of the community service activities have had a positive impact. Data from the pre-test and post-test showed an increase on a scale of 1-5 from 4.6 to 4.7. Although not very significant, this still indicates that students have a fairly good basic understanding, and this outreach activity can strengthen and clarify that understanding.